Quand Proust Épistolier dialogue avec ses Éditeurs. - Fraisse, Luc (Revue d'Ètudes Proustiennes, 2026)
This article analyzes the correspondence between Marcel Proust and his publishers, highlighting the epistolary exchanges that document the material and editorial genesis of his major work, *In Search of Lost Time*. It draws notably on three collections of unpublished or partially known letters with the publishing houses Calmann-Lévy, Bernard Grasset, and Gallimard, as well as on archives preserved at the National Library of France. These correspondences reveal the difficulties related to publication, contractual negotiations, and interactions with editorial staff, while emphasizing the importance of these exchanges for understanding the creative process and the reception of the work. The article also discusses the intellectual relationship between Proust and Jacques Rivière, which offers a profound aesthetic reflection on the work, notably by addressing the connections and distinctions between Proust’s thought and the philosophy of Henri Bergson.